Promoting Mental Health Through Campus Landscape Design: Insights from New Zealand Universities - Yuqing He; Jacky Bowring; Gillian Lawson (Architecture)
Mental health challenges among university students and staff are a pressing concern globally and in Aotearoa, New Zealand. Despite adopting frameworks like the Okanagan Charter to promote health and well-being, there is a lack of empirical research on how campus landscapes contribute to mental health promotion. This is a preliminary study based on a Ph.D. research project aiming to investigate the role of campus landscapes in supporting relaxation and internal recovery through everyday activities. We conducted a comparative multi-case study involving 66 participants from the University of Auckland, Lincoln University, and the University of Otago, exploring how they use and prefer campus landscapes for relaxation. Our findings indicate that ‘enjoying nature’ is the most preferred relaxation activity, with participants engaging both actively and passively with various spaces such as gardens, open lawns, and forested areas. Additionally, in campus settings, the proximity of relaxation spaces appears to be more important than design quality because of the limited time during working hours, which points to the importance of thoughtful campus planning. This study also found that university staff are often overlooked in discussions about healthy universities, despite their significant role in the campus setting. Overall, this study highlights the importance of biophilic design principles in creating health-promoting campus environments and offers initial insights for integrating natural elements into campus planning to enhance mental health and well-being.